2020
DOI: 10.22161/ijeab.56.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Growth Promoting Rhizobacteria (PGPR) on Increasing the Activity of Defense Enzymes in Tomato Plants

Abstract: Growth-promoting rhizobacteria are non-pathogenic bacteria that can induce plant defense through induction of systemic resistance which can then activate defense enzymes such as Polyphenol Oxidase (PPO), Peroxidase (PO) and Penil Alanine Amoliase (PAL). This study aims to determine the activity of the PPO, PO and PAL defense enzymes with selected PGPR isolates. This research was carried out at the Microbiology and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Rhizobacteria induce systemic resistance by activation of various defense related enzymes peroxidase (PO) and polyphenol oxidase (PPO). Increased activity of PO or PPO has been elicited by biocontrol agent strains in different plants (Govindappa et al, 2010;Nogueira de Moura Guerra et al, 2013;Joni et al, 2020). Research work has reported that the bio-agents P. fluorescens and Bacillus species might stimulate the production of biochemical compounds associated with the host defense (Kavino et al, 2007;Raj et al, 2016;Rais et al, 2017).…”
Section: Discussiᴏnmentioning
confidence: 99%
“…Rhizobacteria induce systemic resistance by activation of various defense related enzymes peroxidase (PO) and polyphenol oxidase (PPO). Increased activity of PO or PPO has been elicited by biocontrol agent strains in different plants (Govindappa et al, 2010;Nogueira de Moura Guerra et al, 2013;Joni et al, 2020). Research work has reported that the bio-agents P. fluorescens and Bacillus species might stimulate the production of biochemical compounds associated with the host defense (Kavino et al, 2007;Raj et al, 2016;Rais et al, 2017).…”
Section: Discussiᴏnmentioning
confidence: 99%
“…secreted multiple biocontrol determinants such as glucanase (1.0-1.3 U/mg of soil), protease (1.1-5.5 U/mg of soil), siderophores (6.5-42.8 µg/mL) in rhizosphere of rice varieties thus alleviating P. oryzae induced oxidative damage and suppressing blast disease incidence. Application of PGPR strains especially fluorescent Pseudomonads in horticultural crops such as tomato, chilli and banana expressed increased activity of PPO and its isoforms, when challenged by viruses such as Tomato spotted wilt virus, Cucumber mosaic virus and Banana bunchy top virus (Joni et al, 2020).…”
Section: Polyphenol Oxidase (Ppo)mentioning
confidence: 99%
“…Peroxidase leads to the polymerization of phenolic compounds into lignin-like substances, impeding pathogen growth 34 . Polyphenol oxidase catalyzes phenolic compounds into antimicrobial quinones, playing a vital role in plant defense 35 . Phenylalanine ammonia lyase connects primary and secondary metabolism, catalyzing the synthesis of phenolic compounds crucial for resistance against pathogens 36 .…”
Section: Introductionmentioning
confidence: 99%